Understanding democracy : a hip pocket guide - Patrick, John J., 1935- (Oxford University Press, 2006)
This handy pocket guide explains the core concepts of democracy in a clear A-Z format. Though these core concepts may be practiced differently in various countries, every genuine democracy is based on them in one way or another. Ideal for civics and government classrooms, Understanding Democracy is a concise, scholarly starting point for research papers and writing assignments.